TCAD simulation of radiation-induced leakage current in 1T1C SDRAM. (September 2018) - Nguyen, Hoang T.; Rodriguez, A.; Wrobel, F.; Michez, A.; Bezerra, F.; Chatry, N.; Vandevelde, B.
Abstract: In order to identify the physical mechanism of retention time drop in irradiated SDRAM cell, we implemented the Gossick model of displacement damage cluster into a TCAD simulation tool. Simulation results show that the cluster's position is the key parameter of the phenomenon. Besides that, obtained results are coherent with previous studies and explained by semiconductor physics. Other technological parameters of the cell also influence its response to displacement damage clusters. Leakage current induced by clusters depends exponentially on temperature. Highlights: 1D simulation of the storage node on DRAM cell has been performed with TCAD software. Monitoring the leakage current of the DRAM cell with the influence of defect cluster in Gossick model Study shows the leakage current increases fast when the cluster of defect stays inside the depletion region. Temperature increases the leakage current through the storage node. Technological parameters of DRAM such as applied voltage, doping profile will affect the sensitive region of the phenomenon.